Preparation and characteristic analysis of nanofacula array - Lina Shao (Nature Portfolio, 2021)
Abstract The development of nanofacula array is an effective methods to improve the performance of Near-field Scanning Optical Microscopy (NSOM) and achieve high-throughput array scanning. The nanofacula array is realized by preparing metal nanopore array through the "two etching-one development" method of double-layer resists and the negative lift-off process after metal film coating. The shading property of metal film plays important rules in nanofacula array fabrication. We investigate the shading coefficient of three kinds of metal films (gold–palladium alloy (Au/Pd), platinum (Pt), chromium (Cr)) under different coating times, and 3.5 min Au/Pd film is determined as the candidate of the nanofacula array fabrication for its lower thickness (about 23 nm) and higher shading coefficient (≥ 90%). The nanofacula array is obtained by irradiating with white light (central wavelength of 500 nm) through the metal nanopore array (250/450 nm pore diameter, 2 μm pore spacing and 7 μm group spacing). Moreover, the finite difference and time domain (FDTD) simulation proves that the combination of nanopore array and microlens array achieves high-energy focused nanofacula array, which shows a 3.2 times enhancement of electric field. It provides a new idea for NSOM to realize fast super-resolution focusing facula array.